Securing the development and delivery of modern applications - Bašić, Matej; Morić, Zlatan; Redžepagić, Jasmin; Torbar, Josip (Edelweiss Applied Science and Technology, 2025)
This study analyzes the significant difficulties and solutions for ensuring the security of developing and deploying contemporary software applications in the current fast-paced technological landscape. It examines the escalating hazards linked to expedited software delivery cycles via agile and DevOps methodologies, emphasizing critical domains such as static code analysis, CI/CD pipeline security, container image scanning, and container platform security. This research consolidates findings from existing studies and practical case scenarios, assessing the efficacy of SonarQube, Clair, Trivy, and Kube-bench in detecting vulnerabilities, improving operational efficiency, and guaranteeing adherence to industry standards. Case studies, such as Skyscanner's implementation of SonarQube and DAZN's utilization of Checkmarx, underscore the concrete advantages of incorporating sophisticated security protocols. The results underscore the significance of multi-tiered security approaches and highlight prospects for utilizing artificial intelligence to improve vulnerability identification and real-time surveillance. This paper offers practical recommendations to assist organizations in tackling current security issues and anticipating future threats.